An enhancement of reverse-delete algorithm in application of plat map deployment program - Carausos, Peb Marco and Sepnio, Jose Lorenzo D. 4 0 16; 5 (2010)
ABSTRACT: Reverse-delete algorithm - is an algorithm in graph theory used to obtain a minimum spanning tree for each disconnected part of the graph. The set of these minimum spanning trees is called a minimum spanning forest, which contains every vertex in the graph. Descriptive research is used in this study. There are modifications on the enhanced algorithm. These changes are made to answer the problems and meet the proponents objectives. Further Enhancement is applied to improve the algorithms performance. This research shows that the algorithm can be used to help improve applications such as the text editor that is very common and useful nowadays.
Undergraduate Thesis: (Bachelor of Science in Computer Science)- Pamantasan ng Lungsod ng Maynila, 2010.
Keywords: 2 -- 0; 6; 20; 20; 2